Antidepressants and COVID-19: case report and literature review - Dabetic, Marija; Nesic, Milica; Dabetic, Uros; Latas, Milan (Engrami, 2022)
Introduction. Anti-inflammatory potential of antidepressants was observed before the COVID-19 pandemic. However, it recently regained spotlight when studies with large number of patients showed that antidepressants reduced the risk of intubation and death in COVID-19 symptomatic infection. Also, the response to antidepressants seems to be more rapid in post-COVID depression that in non-COVID19 related depression. The aim of this paper to review the literature regarding the effects and mechanisms of action of antidepressants in COVID-19 infection and post-COVID sequalae, and to present a case repot of a typical outpatient with post-COVID depression.Conclusion. Post-COVID depression is a common sequela of COVID-19 infection. Selective serotonin reuptake inhibitors elicit a rapid and efficient response in patients with post-COVID depression, which may be explained by their anti-inflammatory properties. Timely screening and treatment of post-COVID psychiatric disorders can significantly decrease the burden of COVID-19 pandemic both at the individual and societal level. Also, it is discussed how the pandemic studies of antidepressant mechanisms of actions provided new insights on the aetiology of depression.
Keywords: serotonin; inflammation; cytokines; SSRI; escitalopram; SARS-CoV-2